Documents from Stasys Žakevičius (Žymantas) archive - Juodis, Darius (Genocidas ir rezistencija, 2012)
In 2009, the Museum of Genocide Victims of the Genocide and Resistance Research Centre of Lithuania received documents from the archive of Stasys Žakevičius (who was called Žymantas since 1945), a social activist, lawyer, and participant of the anti-Soviet and anti-Nazi resistance, from the United States of America. The documents from the archive collected and preserved by Žakevičius have not yet been used much in historical research, as they are scattered in various archives and reflect different periods of his biography.